The Shape Synthesis of Transmitarray Antenna Elements - Aljanah, Abdullah Saad A (Université d'Ottawa / University of Ottawa, 2020)
Shape synthesis (also called topological synthesis or inverse design in other disciplines) has the potential to provide antenna engineers with a useful addition to their design tools. Transmitarray antennas, which consist of a feed antenna plus a printed planar structure that emulates a lens, are able to provide high directivity antenna performance, and have been the subject of sustained research over the past ten years. The transmitarray lens consists of a lattice of cells, with each cell occupied by an element that includes conductors of specific shape. The feed field incident on each element on the input surface side of the transmitarray is transformed by each element into a field of different amplitude and phase on the output surface side of each element, providing some desired aperture distribution on the output surface. In this thesis we develop a technique, and the overall computational tool to implement it, that fundamentally allows the electromagnetics to dictate how the conducting portions of a 3-layer element must be shaped in order to obtain some specific transmission coefficient. Such shape synthesis of the elements offers the possibility of obtaining elements that have properties not obtainable using conventional elements. These techniques were applied to the shape synthesis of dual-band elements (18 GHz and 24 GHz). A transmitarray using these elements was designed and fabricated, its performance measured and compared to simulated results. An in-depth discussion of the outcome experimentally validates the shape synthesis procedure.
Keywords: transmitarray; elements; 3-layer; shape synthesis